Communication of CSR activities : a case study in the dairy sector - Adldoost, Maryam (SLU/Dept. of Economics, 2012)
Recent corporate challenges require effective communication in order to secure a company’s reputation. Companies as a result, need to be committed to a series of corporate social and environmental practices along with their financial commitments to their shareholders and investors. In fact, businesses are required to go above their ordinary operations and involve all potential stakeholders that can be affected by their strategies. Companies also need to communicate social, environmental and economic consequences of their activities along with their CSR commitments to their internal and external stakeholders in order to make a better corporate image and improve their market opportunities. Currently, non-financial reporting of CSR has developed and made CSR reports a more permanent part of business reporting context. Through different industries, the food sector can gain increased insights about incorporation of CSR in its value chain, since food products are based on natural resources, such as animal and plants and they fulfil one of the basic human requirements. Moreover, this industry is very labour intensive that connects it with the argument of paying fare prices to the producers and improving the work condition for them. This paper focuses on communicated corporate social responsibility reports of two case companies, Arla and Valio, in order to provide an overview about CSR themes and topics in the dairy industry as a significant part of the food industry. The paper intends to identify concerned stakeholders and communicated outcomes of CSR activities. A qualitative case study is applied in order to collect data, build a relationship and make appropriate interpretations. Besides, the triple bottom line, stakeholder theory and CSR communication framework is chosen as theories of data analysis and in order to generate results. The secondary data of the case companies shows that these companies communicate same areas of responsibility and state similar activities with minor differences in the structure of their CSR reports. These areas are linked to six major themes that are: primary production, procurement, product safety as well as social, environmental and financial responsibilities. The key stakeholders of the case companies were also identified, since it is important for companies to observe the fluctuating and multidimensional environment of their business to serve and satisfy the needs of the society in which they operate. The analysis of the empirical data is concluded with identification of communicated outcomes of CSR activities.